2013
DOI: 10.1007/s13762-013-0412-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances in microbial bioremediation and the factors influencing the process

Abstract: Irrational and rapid global human societal development has culminated to a condition of environmental deterioration. Accidental leakage and deliberate use of organic and inorganic chemicals have contaminated the environment up to the level of ecosystem. Advancements have been made in the field of research on bioremediation of the hazardous contaminants especially in last three decades. Microbial bioremediation has been the most understood biotechnological process of environmental restoration. Bacteria and fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 130 publications
0
30
0
1
Order By: Relevance
“…Moreover, molecular techniques such as denaturing gradient gel electrophoresis (DGGE) and terminal restriction fragment length polymorphism (TRFLP) fingerprints of PCR amplified 16S rDNA fragments can easily provide the information of overall pattern of microbial community of biofilm (Truu et al 2009). Metagenomics studies revealed that microbes perform well in the community, i.e., consortia (Srivastava et al 2014). In general, microbial communities in a biofilm provide plenty of opportunities to bacterial cells for exchange of genetic information through horizontal gene transfer (HGT) conferring resistance, tolerance and chemical degrading ability (Srivastava et al 2014).…”
Section: Microbial Assemblage (Biofilm) and Its Role In Aquatic Ecosymentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, molecular techniques such as denaturing gradient gel electrophoresis (DGGE) and terminal restriction fragment length polymorphism (TRFLP) fingerprints of PCR amplified 16S rDNA fragments can easily provide the information of overall pattern of microbial community of biofilm (Truu et al 2009). Metagenomics studies revealed that microbes perform well in the community, i.e., consortia (Srivastava et al 2014). In general, microbial communities in a biofilm provide plenty of opportunities to bacterial cells for exchange of genetic information through horizontal gene transfer (HGT) conferring resistance, tolerance and chemical degrading ability (Srivastava et al 2014).…”
Section: Microbial Assemblage (Biofilm) and Its Role In Aquatic Ecosymentioning
confidence: 99%
“…Metagenomics studies revealed that microbes perform well in the community, i.e., consortia (Srivastava et al 2014). In general, microbial communities in a biofilm provide plenty of opportunities to bacterial cells for exchange of genetic information through horizontal gene transfer (HGT) conferring resistance, tolerance and chemical degrading ability (Srivastava et al 2014). Moreover, HGT is often held responsible for enhancing the competitiveness of bacteria in the natural environments (Ventura et al 2007).…”
Section: Microbial Assemblage (Biofilm) and Its Role In Aquatic Ecosymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that hydrocarbon biodegradation can occur over an extensive range of temperatures, the rate of biodegradation usually declines with the diminishing temperature. It also has a major effect on microbial metabolism and consequently on microbial activity in the environment (Srivastava et al, 2014).…”
Section: Temperaturementioning
confidence: 99%